Explanation:
It ain't that hard. Let's take the first one:
y = 4x + 2z
If you wanna make x the subject, you try to get rid of anything by its side. In other words:
![y = 4x + 2z \\ y - 2z = 4x + 2z - 2x \\ y - 2z = 4x \\ (y - 2z)/(4) = (4x)/(4) \\ x = (y - 2z)/(4)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/j1fnzwxilii8l7v2a5ajgckxilhtxvfhnu.png)
Everything boils down to 2 easy steps:
- add or substract to get rid of all the other terms near what you want
- devide by the coefficient
Now let's check the second example:
![z = (x)/(4) + 2 \\ z - 2 = (x)/(4) \\ 4 * (z - 2) = 4 * (x)/(4) \\ x = 4(z - 2)](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zsqu4nnau4l7uowmf7s80q8qkx7l2bv12e.png)
That's it :)
If you have any questions please feal free to ask